2003
DOI: 10.1016/s0046-8177(03)00176-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors in locally advanced rectal cancer treated with preoperative hyperfractionated and accelerated radiotherapy

Abstract: Colorectal cancer is a significant cause of morbidity and mortality in Western populations. More than 1/3 of cases occur in the rectum, with an outcome after surgery less favorable than for colon cancer, as reflected in local recurrence rates of 20% to 50% after traditional surgical treatment. 1 Moreover, rectal cancer is characterized by a higher incidence of regional lymph nodes and distant metastases. Preoperative radiotherapy has been shown to reduce local failure rates and to improve overall survival. 1-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…However, some researchers argued that CRM <2 mm was associated with a negative prognosis 18, 19, 20, 21, 22. A CRM clearance of >5 mm and 0.4 mm was proposed by Kelly et al1 in 2009 and Beaufrère et al23 in 2017, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some researchers argued that CRM <2 mm was associated with a negative prognosis 18, 19, 20, 21, 22. A CRM clearance of >5 mm and 0.4 mm was proposed by Kelly et al1 in 2009 and Beaufrère et al23 in 2017, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The criterion to define a positive CRM remains unclear. However, some researchers believed that CRM within 2 mm was associated with a negative prognosis 18, 19, 20, 21, 22. In addition, Kelly et al1 argued that a CRM clearance >5 mm should be achieved to optimize curative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the analysis, they found that in addition to there being an increased proportion of mucinous tumours found following neo-adjuvant treatment, this was further enhanced in the group with chemo-and radiotherapy than just pre-operative radiotherapy alone [36]. This phenomenon is not fully understood; however, one explanation offered by the College of American Pathologists is that mucinous change is a feature of response to pre-operative treatment [33].…”
Section: Radiological Diagnosis and Measuring Responsementioning
confidence: 99%
“…For example, they are identified as mucinous on biopsy and/or MRI as well as on the surgical resection specimen. These tumours appear to have the worst prognosis and increased risk of local recurrence [33,34]. The documentation of the extent of residual cellular mucin is important since the risk of tumour spillage from such mucin pools will increase the risk of local recurrence.…”
Section: Radiological Diagnosis and Measuring Responsementioning
confidence: 99%
“…The value of ypT parameter equal or higher than uT indicates lack of tumor regression [11,14,[17][18][19][20][21] . This parameter may also be applied to the regression of metastatic regional lymph nodes in rectal cancer, "N-downstaging" [17,20,[22][23][24][25][26] .…”
Section: Colorectal Cancermentioning
confidence: 99%